THE EFFECT OF GIVING DIFFERENT TYPES OF LIME ON THE SPAWNING OF RAINBOW BOESEMAN FISH (MELANOTAENIA BOESEMANI) - Mulyani, Laily Fitriani; Citra Rahmadani, Thoy Batun (JURNAL LEMURU, 2025)
This study aims to analyze the effect of various types of lime on the success of spawning and growth of Rainbow Boesemani fish larvae (Melanotaenia boesemani). The method used was an experiment with a completely randomized design (CRD), involving the treatment of CaCO₃, CaMg(CO₃)₂, MgCO₃, and control, each repeated three times. Data were collected and analyzed using analysis of variance (ANOVA) and the calculation of mineral administration efficiency based on the ratio of the number of larvae produced to the total potential larvae. The results showed that the administration of CaMg(CO₃)₂ produced the highest efficiency of 96.12% with the number of larvae reaching 248, followed by MgCO₃ with an efficiency of 90% and the number of larvae 225. At the same time, CaCO₃ produced the highest number of larvae (923) but the rate of larval mortality was also quite high, and its efficiency reached 24.6%. In addition, the measured water quality showed that the CaMg(CO₃)₂ treatment was able to maintain the pH and mineral stability of the water optimally, which contributed to the successful reproduction and survival of the larvae. Based on these results, the administration of CaMg(CO₃)₂ and MgCO₃ is suggested as an effective mineral material in increasing the success of Rainbow Boesemani fish spawning sustainably. This study emphasizes the importance of mineral adjustment in the aquaculture environment to increase the productivity and efficiency of ornamental fish cultivation.